2019
DOI: 10.26803/ijlter.18.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Total Physical Response (TPR): How is it used to Teach EFL Young Learners?

Abstract: When teachers teach the English vocabulary about parts of the body, they use rhythm and body movements while mentioning its name. It is called Total Physical Response (TPR) method. This article investigates the implementation of the TPR method used by three teachers in teaching English vocabulary to young learners. Additionally, the researchers investigated the problems faced by the three teachers as well as potential solution for those problems. In this research, the researchers used qualitative descriptive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
10
1
1
Order By: Relevance
“…In addition, all three inputs should be sufficiently exposed, so that children can obtain adequate input needed to have a good EFL command. This finding is not the same opinion with Astutik et al (2019) stating that English has a significant effect towards EFL learners even though it is not used as much as the learners' L1.…”
Section: Interrogative Sentence Formscontrasting
confidence: 59%
“…In addition, all three inputs should be sufficiently exposed, so that children can obtain adequate input needed to have a good EFL command. This finding is not the same opinion with Astutik et al (2019) stating that English has a significant effect towards EFL learners even though it is not used as much as the learners' L1.…”
Section: Interrogative Sentence Formscontrasting
confidence: 59%
“…At the foundation of these strategies are teachers' energy, animation, and interest, all of which lead to the positive, industrious attitude noticed in their courses. Astutik et al (2019) also found that teachers who teach English to young learners in rural areas can continue to teach as long as they can be adaptive to all situations and conditions around them. No matter how good a method or strategy is, it will not work well if the teacher themself cannot adapt to their environment and the characteristics of their students.…”
Section: Teaching Efl To Young Learners In Difficult Circumstancesmentioning
confidence: 97%
“…Difficult conditions include the lack of learning facilities, mainly in today's digital era, and the demographic diversity in which students and teachers live, especially in the rural areas. Several researchers have attempted to examine good practice in difficult circumstances by interviewing and observing primary school teachers in various countries (Alyasin, 2018;Astutik et al, 2019;Binod, 2015;Garton et al, 2011;Khulel, 2021;Kuchah, 2018).…”
Section: Teaching Efl To Young Learners In Difficult Circumstancesmentioning
confidence: 99%
“…This theory is not a new issue in the field of English Language Teaching. Numerous experts and research have revealed that children’s age is a golden age where their memory is still strong, they are easy to receive information, and they have much time to learn new things ( Moon, 2005 ; Schröter and Danielsson, 2016 ; Astutik et al, 2019 ; Xolmurodova, 2021 ). This issue is undoubtedly different from people who have grown up learning English as a foreign language or second language.…”
Section: Literature Reviewmentioning
confidence: 99%